Investigations of geometrical structure and morphology of samples made of hard machinable materials after wire electrical discharge machining and vibro‐abrasive finishing. Issue 5 (9th May 2019) - Gołąbczak, M.; Maksim, P.; Jacquet, P.; Gołąbczak, A.; Woźniak, K.; Nouveau, C.
Abstract: In this article the results concerned influence of processing conditions of the wire electrical discharge machining and vibro‐abrasive machining on the surface layer and morphology of samples made of hard machinable materials used in aircraft industry like: Titanium 5553 β, Inconel 617, Hastelloy X and Magnesium AZ31 have been presented. For this purpose the cubic and cylindrical samples made of hard machinable alloys have been prepared using optimal electric parameters of wire‐cut electrical discharge machining and finally they have been polished using circular vibratory finishing technology and different ceramic shaped stones. Translation abstract: Im Artikel werden Untersuchungsergebnisse von schwer zu bearbeitenden Metalllegierungen aus der Flugzeugindustrie nach dem Einsatz von elektroerosivem Drahtschneiden und der Vibrationsschleiftechnik in Bezug auf Rauheit und Oberflächenstruktur dargestellt. Zu diesen gehören: Titan 5553 ß‐Legierung, Inconel 617, Hastelloy X und Magnesium AZ31‐Legierung. Zu diesem Zweck wurden Proben in Würfel‐ und Zylinderform mit elektroerosivem Drahtschneiden ausgeschnitten und mittels der Vibrationsschleiftechnik unter Anwendung von keramischen Schleifmitteln fertigbearbeitet.